TOGAF ADM to Improve The Promotion of Farm Edu-Tourism in Pondok Rangon Area - Sari, Tri Retna; Rahmawati, Eva; Harafani, Hani (Politeknik Ganesha Medan, 2019)
Edu-tourism is the one of the most popular sub-type of tourism these days,where many countries in the world use Edu-tourism as one of the main sources of income. However, the lack of promotion with such a good planning and good infrastructure makes Edu-tourism on farms less attractive. In this research we try to build a plan to develop an information systems architecture in the Pondok Rangon ranch area to analyze operational activities on the ranch, designing information system development architecture using TOGAF ADM, and make a system information enterprise architecture design model that can be used as one of the facility to optimize the development of the promotion of the educational tourism industry on livestock especially the Pondok Rangon area. This research is only limited to the preliminary phase up to the technology phase so that the next research is expected to meet all the TOGAF ADM phases.